Tourism in Norrbotten, Sweden : A better understanding of tourism and its future – from the organizations perspective - Öhman, Rebecca; Sandlund, Karin (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
The tourism industry is one of the fastest growing industries in the world and the growth of tourism in the northernmost county of Sweden, Norrbotten, has been evident in recent years. With this rapid growth within tourism in Norrbotten, a reflection arises of why tourism is increasing to this extent. Therefore, this study’s purpose was to get a better understanding of what the core of exclusiveness is for tourism in Norrbotten and how tourism can flourish and grow while keeping the place unique and exclusive. In order to fulfill this purpose, two research questions were stated as follows: “What features make tourism in Norrbotten exclusive?” and “How can tourism in Norrbotten grow without risking overcrowding?”. To answer these questions, a frame of reference was established based on the previous literature within the subject. The study conducted a qualitative approach which allowed the authors to collect data through semi-structured interviews. The two interviews were conducted with two organizations located in Norrbotten County. Swedish Lapland and Pine Bay Lodge. By interviewing one person from each company, the authors received relevant information that gave a better understanding regarding the study. Thereafter, a comparison between frame of reference and the collected data could be done. The results suggested that it is of utmost importance to have a strategy regarding overcrowding. Furthermore, it could be stated that the nature and natural assets Norrbotten possess, is a key for success. Nevertheless, the importance of providing the tourist with excellent hospitality cannot be forgotten, as this creates an even higher feeling of exclusiveness. Turism industrin är en av de snabbast växande industrierna i världen och tillväxten av turism i Sveriges nordligaste län, Norrbotten, har varit tydlig under de senaste åren. Detta skapar en nyfikenhet kring varför turismen i just Norrbotten har ökat i denna utsträckning. Därför var syftet med denna studie att få en djupare förståelse för vad kärnan inom turismen ...